2023
DOI: 10.3389/fendo.2023.1102670
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates and metabolic indicators of elevated fasting glucose in overweight/obese Chinese Han patients with first-episode and drug-naive major depressive disorder

Abstract: BackgroundOverweight/obese major depressive disorder (MDD) patients have a high probability of developing glucose metabolism disorders; however, the results are inconsistent due to the confounding variables involved in the studies. The purpose of this study was to explore the prevalence and risk factors for elevated fasting glucose in Chinese Han patients with overweight/obese first-episode and drug naïve (FEDN) MDD.MethodsThe study used a cross-sectional design and recruited 1718 FEDN MDD patients between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 52 publications
0
4
2
Order By: Relevance
“…25,[41][42][43][44][45][46][47][48][49] We also found that the hyperglycemic subgroup had a shorter duration of disease and a lower level of education. However, these did not differ significantly in some other studies, 24,34 which may be related to differences in the study population and for the classification of education level.…”
contrasting
confidence: 63%
See 4 more Smart Citations
“…25,[41][42][43][44][45][46][47][48][49] We also found that the hyperglycemic subgroup had a shorter duration of disease and a lower level of education. However, these did not differ significantly in some other studies, 24,34 which may be related to differences in the study population and for the classification of education level.…”
contrasting
confidence: 63%
“… 27 Elevated TSH levels and TG levels are consistent with the results of other studies. 34 , 41 Thyroid hormone function is closely related to glycemia, and elevated TSH levels in particular may cause metabolic abnormalities in MDD patients, including elevated blood glucose, obesity, elevated LDL-C, and metabolic syndrome. 25 , 41 , 42 TSH may cause insulin resistance and glucose dysregulation, where mechanisms include hepatic endoplasmic reticulum stress, 42 , 50 endothelial dysfunction, and inhibition of lipid triglyceride lipase leading to increased TG stores, 51 , 52 among others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations